Analysis of Low Back Pain Symptoms Felt by Intercity Bus Drivers - Mayasari, Ema; Ramadhani, Firda Puspa Ringga (Universitas STRADA Indonesia, 2025)
Low back pain (LBP) is a common lower back pain felt by bus drivers due to the static sitting position they use during work. This study aims to explore the causes of LBP symptoms felt by intercity bus drivers, focusing on travel distance and rest periods during work. The research method used was a qualitative case study. The informants were intercity bus drivers (Tulungagung-Surabaya) selected using purposive sampling. Data collection techniques included in-depth interviews, participant observation, documents, archival recordings, and physical device observations. The results of the study indicate that workers typically work 10–12 hours per day, traveling approximately 300 km round trip. Rest periods vary, from 2–6 hours per round trip, but are not always sufficient for physical recovery. Lower back pain is a common complaint due to prolonged sitting and fatigue, and is rarely treated medically. The dominant self-management strategies include rest, massage, drinking water, or herbal medicine. Management is advised to more structure driver driving and rest schedules in accordance with occupational safety standards. Regulators are also expected to monitor work hours and provide education on ergonomics and occupational health to minimize the risk of low back pain and maintain the safety and quality of transportation services.